Annual incidence of inflammatory joint diseases in a population based study in southern Sweden. Issue 10 (1st October 2002) - Söderlin, M K; Börjesson, O; Kautiainen, H; Skogh, T; Leirisalo-Repo, M
Abstract : Objective: To estimate the annual incidence of inflammatory joint diseases in a population based prospective referral study in an adult population in Kronoberg County in southern Sweden. Methods: The patients were referred from primary healthcare centres to the rheumatology department in Växjö Central Hospital or to the one private rheumatologist in Växjö participating in the study. Additionally, the hospital records for patients with joint aspirates during the inclusion period were checked. The patients were registered as incident cases if the onset of the joint inflammation was between 1 May 1999 and 1 May 2000. A systematic follow up of incoming referrals was conducted up to 31 January 2001. Children under the age of 16 and patients with septic arthritis, crystal arthropathies, and osteoarthritis were excluded from the study. Results: A total of 151 new cases with inflammatory joint diseases were identified during one year, corresponding to a total annual incidence of 115/100 000. Of these, 31 patients (21%) had rheumatoid arthritis, the annual incidence being 24/100 000 (for women 29/100 000, and for men 18/100 000). Reactive arthritis was diagnosed in 37 patients (24%, annual incidence 28/100 000) and 54 patients had undifferentiated arthritis (36%, annual incidence 41/100 000). Eleven patients presented with psoriatic arthritis (7%, annual incidence 8/100 000). The incidence of Lyme arthritis was small in this non-endemic area, and the incidence of sarcoid arthritis corresponded to that in earlier studies. Conclusion: This is the first prospective population based annual incidence study of early arthritis in Sweden. In this population, 36% of the incident cases had undifferentiated arthritis, whereas rheumatoid arthritis and reactive arthritis accounted for 45% of the cases. The incidence figures compare well with figures reported from other countries.